Special ops host and network security for Microsoft, UNIX, and Oracle - Birkholz, Erik Pace.; McClure, Stuart (Rockland, Mass. : Syngress Pub., 2003)
Special Ops: Internal Network Security Guide is the solution for the impossible 24-hour IT work day. By now, most companies have hardened their perimeters and locked out the "bad guys," but what has been done on the inside? This book attacks the problem of the soft, chewy center in internal networks. We use a two-pronged approach-Tactical and Strategic-to give readers a complete guide to internal penetration testing. Content includes the newest vulnerabilities and exploits, assessment methodologies, host review guides, secure baselines and case studies to bring it all together. We have scoured the Internet and assembled some of the best to function as Technical Specialists and Strategic Specialists. This creates a diversified project removing restrictive corporate boundaries. The unique style of this book will allow it to cover an incredibly broad range of topics in unparalleled detail. Chapters within the book will be written using the same concepts behind software development. Chapters will be treated like functions within programming code, allowing the authors to call on each other's data. These functions will supplement the methodology when specific technologies are examined thus reducing the common redundancies found in other security books. This book is designed to be the "one-stop shop" for security engineers who want all their information in one place. The technical nature of this may be too much for middle management; however technical managers can use the book to help them understand the challenges faced by the engineers who support their businesses. ΆUnprecedented Team of Security Luminaries. Led by Foundstone Principal Consultant, Erik Pace Birkholz, each of the contributing authors on this book is a recognized superstar in their respective fields. All are highly visible speakers and consultants and their frequent presentations at major industry events such as the Black Hat Briefings and the 29th Annual Computer Security Institute Show in November, 2002 will provide this book with a high-profile launch. ΆThe only all-encompassing book on internal network security. Windows 2000, Windows XP, Solaris, Linux and Cisco IOS and their applications are usually running simultaneously in some form on most enterprise networks. Other books deal with these components individually, but no other book provides a comprehensive solution like Special Ops. This book's unique style will give the reader the value of 10 books in 1.
Foreword by Stuart McClure -- Part I: METHODOLOGY -- Chapter 1: Defining Scope for the Project -- Chapter 2: Identifying Targets -- Chapter 3: High Severity Vulnerabilities -- Chapter 4: Vulnerability Mapping -- Chapter 5: Penetration Techniques -- Part II: TACTICAL -- Chapter 6: Windows 2000 Operating System -- Chapter 7: Windows XP Operating System -- Chapter 8: Windows Active Directory -- Chapter 9: Exchange Server & OWA -- Chapter 10: Terminal Server -- Chapter 11: Microsoft IIS -- Chapter 12: Attacking Web Applications -- Chapter 13: Attacking and Defending SQL -- Chapter 14: Attacking and Defending Oracle -- Chapter 15: Defending UNIX -- Chapter 16: Attacking and Defending Solaris -- Chapter 17: Creating Custom Tools -- Chapter 18: Network Architecture -- Chapter 19: Building and Attacking Wireless Networks -- Part III: STRATEGIC -- Chapter 20: Internal Security Teams -- Chapter 21: Public Source Information -- Chapter 22: Security Policies -- Chapter 23: Internal Education Programs.
Includes index.
Keywords: Firewalls (Computer security); Computer networks -- Security measures; Computer network architectures; Microsoft Windows; UNIX; Oracle; Electronic books